THE IMPLEMENTATION OF USING FLASHCARDS TOWARDS STUDENTS PASSIVE VOICE MASTERY AT THE SECOND SEMESTER OF THE ELEVENTH CLASS OF SMA MUHAMMADIYAH 2 BANDAR LAMPUNG - LINA PURWATI (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2023)
Many students at senior high school up to university found difficulties in learning English especially grammar. Grammar is one of English components that should be mastered by students who learn English because grammar is very valuable and important in using English. Grammar has many items and passive voice is one of grammar items which is very important and valuable to be learned. But in fact, most of graduate students of senior high school found difficulties to master passive voice well. Therefore, the teacher should pay attention to use the appropriate technique for teaching in the class. In this research, the researcher tried to investigate the use of "flashcard" as a teaching media in teaching passive voice. The sample of this research was 36 students of second semester at the eleventh class of SMA Muhammadiyah 2 Bandar Lampung. The hypothesis of this research is the implementation of flashcard can increase the students' passive voice mastery. In this research, the researcher used experimental method. In this research, the researcher used test as a main technique, she had done the observation and library research as supporting techniques. After analyzing the data, the researcher got the result of this research tratio = 7.73 and ttable with the significant level 1 %, it was 2.39. So it is clear that 7.73 > 2.39 which that hypothesis Ho is rejected and hypothesis alternative Ha is accepted. Based on the result, the implementation of using flashcards can improve students' passive voice mastery and the average score of students after being taught by using flashcards is higher than before. So, the implementation of flashcards can increase the students' passive voice mastery. ABSTRAKBanyak siswa di sekolah menengah atas hingga perguruan tinggi mengalami kesulitan dalam mempelajari bahasa Inggris terutama tata bahasa. Grammar adalah salah satu komponen bahasa Inggris yang harus dikuasai oleh siswa yang mempelajari bahasa Inggris karena grammar sangat berharga dan penting dalam menggunakan bahasa Inggris. Grammar memiliki banyak item dan passive voice merupakan salah satu item grammar yang sangat penting dan berharga untuk dipelajari. Namun pada kenyataannya, sebagian besar siswa lulusan SMA mengalami kesulitan untuk menguasai passive voice dengan baik. Oleh karena itu, guru harus memperhatikan untuk menggunakan teknik yang tepat untuk mengajar di kelas. Dalam penelitian ini, peneliti mencoba menginvestigasi penggunaan "flashcard" sebagai media pembelajaran dalam pengajaran passive voice. Sampel penelitian ini adalah 36 siswa semester genap kelas sebelas SMA Muhammadiyah 2 Bandar Lampung. Hipotesis dari penelitian ini adalah penerapan flashcard dapat meningkatkan penguasaan passive voice siswa. Dalam penelitian ini, peneliti menggunakan metode eksperimen. Dalam penelitian ini, peneliti menggunakan tes sebagai teknik utama, dia telah melakukan observasi dan penelitian kepustakaan sebagai teknik pendukung. Setelah dilakukan analisis data, peneliti mendapatkan hasil penelitian ini tratio = 7,73 dan ttabel dengan taraf signifikan 1 % yaitu 2,39. Jadi jelas bahwa 7,73 > 2,39 yang mana hipotesis Ho ditolak dan alternatif hipotesis Ha diterima. Berdasarkan hasil tersebut, penerapan penggunaan flashcards dapat meningkatkan penguasaan passive voice siswa dan nilai rata-rata siswa setelah diajar menggunakan flashcards lebih tinggi dari sebelumnya. Jadi, penerapan flashcards dapat meningkatkan penguasaan passive voice siswa.